3′‐O‐Caged 2′‐Deoxynucleoside Triphosphates for Light‐Mediated, Enzyme‐Catalyzed, Template‐Independent DNA Synthesis. Issue 1 (13th February 2018) - Mathews, Anu Stella; Yang, Haikang; Montemagno, Carlo
Abstract: Synthesis, purification, and characterization of 3′‐ O ‐caged 2′‐deoxyribonucleoside triphosphates (dNTPs), namely 3′‐ O ‐(2‐nitrobenzyl)‐2′‐deoxy ribonucleoside triphosphates (NB‐dNTPs) and 3′‐ O ‐(4, 5‐dimethoxy‐2‐nitrobenzyl)‐2′‐deoxy ribonucleoside triphosphates (DMNB‐dNTPs), are discussed in detail. A total of eight 3′‐ O ‐caged dNTPs are synthesized with specific protocols depending on the nitrogenous base on the first carbon, i.e., adenine, guanine, thymine, and cytosine, as well as the photo‐cleavable group, i.e, 2‐nitrobenzyl and 4, 5‐ dimethoxy‐2‐nitrobenzyl, to be attached in the 3′‐ O position. The purification of the synthesized compounds is done using ion‐exchange and flash chromatography; this is followed by structural confirmation by nuclear magnetic resonance (NMR) and mass spectroscopy (MS). The efficiency of the designed compounds is tested by conducting and evaluating UV‐cleaving experiments at 365 nm with proton NMR and LC‐MS curves. Finally, the application of the 3′‐ O ‐cagged dNTPs in template‐independent, enzyme‐catalyzed, photo‐mediated oligonucleotide synthesis is demonstrated. © 2017 by John Wiley & Sons, Inc.